Navigator, a new endemic genus of Cetoniinae (Coleoptera: Scarabaeidae) from Australia, with descriptions of two new species and behavioural studies - Moeseneder, Christian H.; Hutchinson, Paul M. (Zootaxa, 2016)
The endemic flower beetle genus Navigator new genus (Coleoptera: Scarabaeidae: Cetoniinae: Schizorhinini) is described from Australia. Navigator contains species that are morphologically and behaviourally unusual when compared to the majority of other Australian flower beetles in several easily visible characters. A differential diagnosis with similar Australian schizorhinine genera and species is performed, and a key to its species is provided. Pseudoclithria fossor Lea, 1914 and Pseudoclithria ruficornis (Westwood, 1874) are moved to the genus Navigator, resulting in Navigator fossor new combination, which is designated as the type species, and Navigator ruficornis new combination. A lectotype is designated for Navigator fossor (Lea, 1914). We describe Navigator interior new species, from Central Australia and Navigator pixii new species, which occurs in Queensland and is the smallest Australian Schizorhinini known. Distribution information for all Navigator species is provided. Our observations of Navigator fossor and Navigator pixii show their larvae are free living in soil and feed on decaying leaves, which is the first time such behaviour is described in Australian cetoniines. We observe that three Navigator species are more tolerant of arid climate than most other Australian cetoniines, adults almost never visit flowers, and males are often in flight searching for sedentary females.